2015
DOI: 10.1248/bpb.b14-00517
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the Cell-Penetrating Peptide Penetratin as an Oral Absorption Enhancer

Abstract: Novel delivery technology using cell-penetrating peptides (CPPs) have recently shown their potential and are emerging as promising candidates for an oral protein and peptide delivery systems. As with for the development of any absorption enhancer that is meant to function across an epithelial layer covering a surface highly exposed to pathogens such as the intestines, concern arises about the safety of such enhancers. The purpose of this study was to investigate the effect of 7 d of consecutive oral administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…Chitosan nanoparticles opened TJs and increased intestinal permeability of insulin, but co-administration with LPS (5 mg/kg) to rats for 7 days did not lead to an increase in hepatic necrosis [476]. In a similar study, coadministration of penetratin (5mM) or C 10 (154 mM) with LPS for 7 days to mice had no effect on biomarkers of hepatic necrosis, however taurodeoxycholate (96 mM) increased plasma levels of aspartate transaminase and alanine transaminase [477]. It is noteworthy that uptake of LPS into the hepatic portal vein is not pathological as low level uptake is associated with maintaining a normal responsive kupffer cell population, but excessive levels may lead to hepatic dysfunction [478].…”
Section: The Bystander Absorption Argumentmentioning
confidence: 92%
“…Chitosan nanoparticles opened TJs and increased intestinal permeability of insulin, but co-administration with LPS (5 mg/kg) to rats for 7 days did not lead to an increase in hepatic necrosis [476]. In a similar study, coadministration of penetratin (5mM) or C 10 (154 mM) with LPS for 7 days to mice had no effect on biomarkers of hepatic necrosis, however taurodeoxycholate (96 mM) increased plasma levels of aspartate transaminase and alanine transaminase [477]. It is noteworthy that uptake of LPS into the hepatic portal vein is not pathological as low level uptake is associated with maintaining a normal responsive kupffer cell population, but excessive levels may lead to hepatic dysfunction [478].…”
Section: The Bystander Absorption Argumentmentioning
confidence: 92%
“…The surfactants hexadecylphosphocholine and octylphenol ethoxylate increase permeation of LPS across Caco-2 monolayers [125]. Co-delivery of C 10 (154 mM) or penetratin (2 mM) with LPS to mice for seven consecutive days did not cause LPS induced hepatic damage, as measured by plasma levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) which are both released during hepatic necrosis [126]. A significant elevation in those enzymes was observed when LPS was co-delivered with taurodeoxycholate (96 mM) in the same study.…”
Section: Recent Highlightsmentioning
confidence: 99%
“…When penetratin was also orally co-administered with LPS daily for 7 days in mice, there was no significant increase levels in liver enzymes. 63 Although, one particular study demonstrated an increase in serum LPS after prolonged exposure to food-and pharmaceutical grade emulsifiers, carboxymethylcellulose (1% w/v) or polysorbate-80 (1% w/v) in wild type and IL-10 knock-out mice. 64 However, the foregoing is predicated on the risk for bystander entry solely according to a MW and molecular diameter-based argument.…”
Section: Pe-induced Intestinal Permeability Of Lps and Xenobioticsmentioning
confidence: 99%